Analysis of the Implementation of the Dirt Truck Operating Hours Policy in Tangerang Regency - Misbah, Muhamad; Lesmana, Sri Jaya; Ratna Indayatun (The International Journal of Law Review and State Administration, 2024)
This study aims to analyze the implementation of the policy on operating hours of dirt trucks in Tangerang Regency based on Regent Regulation Number 12 of 2022. This policy was enacted to limit the operating hours of dirt trucks to reduce congestion and improve traffic safety. The research method used is a normative-empirical juridical method with data collection techniques through observation, interviews, and documentation studies. The results of the study show that the implementation of the policy has not been optimal. Despite the regulations that have been set, there are still 10,989 units of dirt trucks that violate operating hours during 2023. Some of the factors that affect the less effective implementation of this policy include the lack of socialization to truck drivers and entrepreneurs, as well as the limited number of officers in the field to carry out supervision and control.